Performance-Based Funding of Universities: Past and Present European Developments - Kivistö, Jussi; Suprun, Kateryna (International Higher Education, 2024)
The article provides an overview of the implementation of performance-based funding (PBF) across the European continent. The cross-country comparison includes both endorsement and proposed rethinking of PBF practices by early adopters (e.g., United Kingdom, Finland, Denmark, and the Netherlands) and latecomers (e.g., Latvia, Ukraine). The authors argue for diversified approaches to PBF depending on system maturity, and for voluntary peer-learning across systems.